Implementasi Gerakan Tangan terhadap Navigasi Robot Beroda menggunakan Teknik Accelerometer - Bagus Prasetyo; Kemahyanto Exaudi; Sarmayanta Sembiring (Universitas Muhammadiyah Surakarta, 2021)
Human-machine interface (HMI) is a system that can connect human organs to the control of a machine using computer technology. Today's robot technology has been widely researched, especially in terms of robot motion control. This research adopts the accelerometer technique by utilizing the wrist to control the motion of a wheeled robot via wireless communication. A wheeled robot as a data receiver and hand movements as a data transmitter. The MPU6050 sensor is mounted on the back of the hand to read hand movements based on the Pitch (y-axis) and Roll (x-axis) values. Communication between robots and hand movements using Bluetooth. The results prove that the accelerometer sensor on the MPU 6050 has successfully identified wrist motion as a remote navigation robot. Pitch value is greater than 160, so the robot moves backward and for moving forward is less than 140. Meanwhile, for moving left, the Roll value is less than 40 and for moving right is greater than 60.